HUBUNGAN POLA PEMBERIAN MP-ASI DAN POLA ASUH GIZI DENGAN STATUS GIZI BAYI USIA 6-23 BULAN, STUDI KASUS DI KELURAHAN LANGENSARI, KECAMATAN UNGARAN BARAT, KABUPATEN SEMARANG - Dwi Kurnia Yuliyawati; Dina Rahayuning Pangestuti; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The problem of nutritional status children are still problem health a lot happening in Indonesia. Children under two are susceptible age group of nutritional status problems causes by supplementary feeding and caring capacity that don't match with age of children under two. The purpose of this research is to know correlation of supplementary feeding and caring capacity with the nutritional status of children under two study of Langensari Village, Ungaran Barat Subsistrict, Semarang District. This research is an quantitative methods, this type of research is an analytic survey with cross sectional design. Population study was children under two, totaling 250 people and the sample was 61 children selected by purposive sampling technique. Data analysis using chi-square test, rank-spearman test, and pearson product moment test. Results showed there was no significant correlation supplementary feeding (p = 0.742), and caring capacity (p = 0.940) with nutritional status of children under two, there was no significant correlation supplementary feeding (p = 0.370) with nutritional status. There was siginificant correlation capacity caring (p = 0.003) with adequate intake of nutrition. There was significant correlation adequacy nutrition level (p = 0.002) with nutritional status of children under two. There was significant correlation family economic status (p = 0,025) with nutritional status of children under two, there was no significant correlation knowledge mother (p = 0,888), infectious disease (p = 0,720), mother's education status (p = 0,401), mother work status (p = 0.599), individual hygiene (p = 0.116) with nutritional status of children under two.